The Role Of Youth-Based Mosque Organization In Counter Radicalism Movement - Zuri Pamuji (Postgraduate Program, Universitas Islam Negeri (UIN) K. H. Abdurrahman Wahid Pekalongan, Indonesia, 2018)
Counter-radicalism is all prevention efforts to build awareness or understanding that radicalism in the form of terror is violence and not related to religious teachings and must be fought together. This research aims to explore conceptually the role of youth-based mosque organization on counter radicalism movement. As for some findings from this research are: first, the core in counter radicalism rests on the function and purpose of the organization. Second, the movement of the organization in counter-radicalisme is divided into three main parts: the guidance and direction, the implementation of various activities of the organization, the control and follow-up of the organization's programs. Third, the role of this organization is more appropriately done in the micro and messo spectrum related the causes of radicalism. The implementation of all efforts requires the active support of stakeholders in society.